Amblyseius largoensis (MUMA), THE ONLY SPECIES COLLECTED TOGETHER WITH THE RED PALM MITE - Ramos, Mayra; Flores-Galano, G.; Rodríguez, H. (Revista de Protección Vegetal, 2010)
Dear Editor: In October19, 2008, in “La Marina”, Santiago de Cuba, and in March 3, 2009, in “El Salvador”, in Guantánamo, both in Cuba, we observed an abundant population of the red palm mite (Raoiella indica Hirst) (Acari:Tenuipalpidae) together a relative profuse population of a predator mite of the Phytoseiidae family on the underside of coconut leaves. Different species of phytoseids were expected to be found, as it was common in other agroecosystems researched by us, but all the taxonomic characters (dorsal shield chetotaxy, ventral setae and shields, legs, chelicerae, spermatheca and spermatodacty shape) had a total coincidence with only one species: Amblyseius largoensis (Muma) (Acari: Phytoseiidae). Hence, we decided to initiate further studies on this species using the red palm mite as food to find out its real role over this invasive alien species.